The Novel Anti-cMet Antibody seeMet 12 Potentiates Sorafenib Therapy and Radiotherapy in a Colorectal Cancer Model - Spiegelberg, Diana; Mortensen, Anja Charlotte Lundgren; Palupi, Kartika Dyah; Micke, Patrick; Wong, Julin; Vojtesek, Borivoj; Lane, David Philip; Nestor, Marika (Frontiers in Oncology, 2020)
Rational: cMet is abnormally regulated in gastrointestinal cancer, and is associated with increased invasiveness of the disease and poor overall survival. There are indications that targeted therapy against cMet, alone or in combination with additional cancer therapies, can help improve treatment outcome. Thus, in the present study we investigated the therapeutic efficacy of a novel cMet-targeting antibody therapy in gastrointestinal cancer models, and assessed potential augmenting effects in combination with tyrosine kinase inhibitor (TKI) targeted therapy or radiotherapy. Methods: Three different cMet-targeting antibodies were first characterized with respect to antigen binding and effects on cell viability in vitro. The best performing candidate seeMet 12 was then further assessed for effects on colorectal cancer cell growth, proliferation and migration. Combinations with the TKI-inhibitor sorafenib or external beam radiotherapy were then evaluated for potential additive or synergistic effects in vitro using monolayer- and multicellular tumor spheroid assays. Finally, the combination of seeMet 12 and radiotherapy was evaluated in vivo in a proof-of-concept colorectal cancer xenograft study. Results: Dose-dependent therapeutic effects were demonstrated for all three cMet-targeting antibodies. Monotherapy using seeMet 12 resulted in impaired cellular migration/proliferation and reduced tumor spheroid growth. Moreover, seeMet 12 was able to potentiate therapeutic effects in vitro for both sorafenib and radiotherapy treatments. Finally, the in vivo therapy study demonstrated promising results, where a combination of seeMet 12 and fractionated radiotherapy increased median survival by 79% compared to radiotherapy alone, and tripled maximum survival. Conclusion: The novel anti-cMet antibody seeMet 12 demonstrated therapeutic effects in cMet positive gastrointestinal cancer cells in vitro. Moreover, the addition of seeMet 12 augmented the effects of sorafenib and radiotherapy. An in vivo proof-of-concept study of seeMet 12 and radiotherapy further validated the results. Thus, cMet-targeted therapy should be further explored as a promising approach to increase therapeutic effects, circumvent treatment resistance, and reduce side effects.